Influence of bone loss and inclination of incisor on periradicular stresses due to simulated bite force - Rodrigues, Samuel; Cortelli, José Roberto; Claro, Ana Paula Rosifini Alves; Chagas, Rosana Villela; ConcÍlio, Lais Regiane Da Silva; Arcas, Luciana Paula Benicio; Claro, Cristiane Aparecida De Assis (Universidade Estadual Paulista Júlio de Mesquita Filho, 2018)
AbstractIntroductionAdults with sequelae of periodontal disease tend to have bone loss, with consequent flaring of the maxillary incisors.ObjectiveThe influence of bone loss and the inclination of the maxillary incisor in the distribution of stresses due to simulated bite forces was studied.Material and methodModels in epoxy resin were made in three conditions (without bone loss and with bone loss of 5mm and 8mm). Increases in the labial inclination of the maxillary incisor of 10° and 20° were obtained with a beveled metallic block. Loads of 100N were applied five times in each condition using a universal test machine. The models were observed and filmed with a circular polariscope. Orders of isochromatic fringes (stresses) on the labial, lingual, and apex surfaces were recorded. The agreement of the data was evaluated using the weighted kappa test, and the results were 0.89 and 0.82 for intra- and inter-examiners, respectively.ResultThe results of the Kruskal–Wallis and SNK tests indicated higher stresses (2.0) with increased labial inclination in the labial surface; higher stresses (2.67) with increased bone loss; higher greater stresses with the association of bone loss and labial-inclination (3.6); and the highest stresses tended to concentrate on the labial surfaces, except in cases of normal inclination and without bone loss (0.45).ConclusionIt was concluded that increases in both the labial inclination of the maxillary incisors and bone loss increase periradicular stresses, and the combination of these factors further increases the stresses due to bite forces, with the highest concentration on the labial side.

ResumoIntroduçãoAdultos com sequelas de doenças periodontais tendem a apresentar perda óssea, com consequente vestibularização dos incisivos superiores.ObjetivoA influência da perda óssea e da inclinação do incisivo superior na distribuição de tensões devido a forças mastigatórias simuladas foram avaliadas nesse estudo.Material e métodoModelos em resina epóxi foram confeccionados em três condições (sem perda óssea e com perda óssea de 5mm e 8mm). Aumentos na inclinação vestibular do incisivo superior de 10° e 20° foram obtidos com um bloco metálico chanfrado. Cargas de 100N foram aplicadas cinco vezes em cada condição usando uma máquina de ensaio universal. Os modelos foram observados e filmados com um polariscópio circular. Ordens de franjas isocromáticas (tensões) nas faces vestibular, lingual e apical foram registradas. A concordância dos dados foi avaliada pelo teste kappa ponderado e os resultados foram 0,89 e 0,82 para intra e interexaminadores, respectivamente.ResultadoOs resultados dos testes de Kruskal-Wallis e SNK indicaram maiores tensões (2,0) com aumento da inclinação vestibular na face vestibular; maiores tensões (2,67) com aumento da perda óssea; maior tensão com a associação de perda óssea e inclinação vestibular (3,6); e as maiores tensões tenderam a concentrar-se na face vestibular, exceto em casos de inclinação normal e sem perda óssea (0,45).ConclusãoConcluiu-se que aumentos tanto da inclinação vestibular dos incisivos superiores quanto da perda óssea aumentam as tensões perirradiculares, e a combinação desses fatores aumenta ainda mais as tensões devido às forças mastigatórias, com a maior concentração na face vestibular.
Influência da perda óssea e da inclinação do incisivo na distribuição de tensões perirradiculares decorrentes da simulação de forças oclusais
Keywords: Tooth migration; bite force; dental stress analysis; bone resorption; Migração dentária; força de mordida; análise de estresse dentário; reabsorção óssea